Comparison of antithrombotic efficacy between edoxaban, a direct factor Xa inhibitor, and fondaparinux, an indirect factor Xa inhibitor under low and high shear rates - Fukuda, Toshio; Tsuji, Naoki; Honda, Yuko; Kamisato, Chikako; Morishima, Yoshiyuki; Shibano, Toshiro (Thrombosis and Haemostasis, 2011)
Edoxaban is an oral, direct factor Xa (FXa) inhibitor under late-phase clinical development. This study compared the antithrombotic efficacy of edoxaban with that of an indirect FXa inhibitor, fondaparinux, in in vivo venous and arterial thrombosis models and in ex vivo perfusion chamber thrombosis model under low and high shear rates in rats. Venous and arterial thrombi were induced by platinum wire insertion into the inferior vena cava and by application of FeCl3 to the carotid artery, respectively. The perfusion chamber thrombus was formed by blood perfusion into a collagen-coated capillary at 150 s-1 (low shear rate) and 1,600 s-1 (high shear rate). Effective doses of edoxaban that reduced thrombus formation by 50% (ED50) in venous and arterial thrombosis models were 0.076 and 0.093 mg/kg/h, respectively. In contrast, ED50 of fondaparinux in the arterial thrombosis model (>10 mg/kg/h) was markedly higher compared to ED50 in the venous thrombosis model (0.021 mg/kg/h). In the perfusion chamber thrombosis model, the ratio of ED50 under high shear rate (1.13 mg/kg/h) to that under low shear rate (0.63 mg/kg/h) for edoxaban was 1.9, whereas that for fondaparinux was more than 66. While the efficacy of fondaparinux markedly decreased in arterial thrombosis and in a high-shear state, edoxaban exerted consistent antithrombotic effects regardless of flow conditions. These results suggest that shear rate is a key factor in different antithrombotic effects between edoxaban and fondaparinux.
Keywords: Edoxaban; factor Xa inhibitor; fondaparinux; shear rate; thrombosis